Scalable synthesis of multilayer h-BN on AlN by metalorganic vapor phase epitaxy: nucleation and growth mechanism. (11th October 2019) - Yang, Xu; Nitta, Shugo; Pristovsek, Markus; Liu, Yuhuai; Liao, Yaqiang; Kushimoto, Maki; Honda, Yoshio; Amano, Hiroshi
Abstract: We studied the nucleation and growth of hexagonal BN (h-BN) on AlN template on c -plane sapphire by metalorganic vapor phase epitaxy as functions of growth temperature, deposition time, and triethylboron (TEB) partial pressure. A lateral growth rate of about 25 nm min −1 for h-BN nuclei was obtained by atomic force microscopy and a nucleation activation energy of 2.1 eV was extracted from the temperature dependence of the nucleation density. A large TEB flow rate strongly enhances the formation of h-BN nuclei. At a reduced TEB flow rate, we observed a significantly decreased nuclei density and a delay in nucleation due to TEB desorption. By fine tuning the growth parameters, single-crystalline multilayer h-BN was successfully formed on AlN surface, as confirmed by x-ray diffraction and transmission electron microscopy (TEM). The epitaxial relationship between h-BN and AlN was [0 0 0 1]h-BN || [0 0 0 1]AlN and [1 0   −1 0]h-BN || [1 1   −2 0]AlN from TEM and electron backscatter diffraction measurements. In addition, TEM showed that the initial h-BN layers are not parallel and tend to form half-domes. On those half-domes (cap-shaped-like) a 2D lateral growth sets on, resulting in a well-oriented 2D multilayer observed in TEM. Thus, the surface topography further develops to form a relatively flat surface without wrinkles and finally a typical hexagon-like wrinkled surface at thicker h-BN layers. Particularly, the small h-BN nuclei have dangling bonds at their periphery that can interact with the substrate, forming actual bonds with AlN. Hence the choice on the substrate is important, despite the basal planes of multilayer h-BN are bonded by a weak van der Waals force.